Evaluasi Sistem Evakuasi Kebakaran pada Kantor Wilayah Direktorat Jenderal Bea Cukai Kalimantan Bagian Selatan - Yasmine Adzkia; Hermin Werdiningsih (Jurnal Sipil dan Arsitektur, 2024)
Banjarmasin is one of Indonesia’s ten provinces that are historically prone to fire. To prevent many life losses due to building fire, a building must comply with existing standards and regulations. Therefore, the fire evacuation system was evaluated at the South Kalimantan Regional Office of the Directorate General of Customs. In this research, the method used is descriptive with an evaluative analysis approach where the building data will be compared to related standards and regulations. From this research, it is proven that several fire evacuation system facilities in the building still do not comply with the existing standards and regulations, such as the number of emergency stairs, emergency exits, and the height of handrails on the stairs.